2001
DOI: 10.1023/a:1011128408146
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and hormonal factors and ovarian cancer

Abstract: This uniquely large study confirms and further quantities the relation between hormonal and reproductive factors and ovarian cancer. The pattern of risk observed cannot be totally explained by a role of ovulation in ovarian carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 21 publications
8
63
1
1
Order By: Relevance
“…The findings on pattern of relative risk for ages 25 and 35 years at delivery are consistent with the results in Pike et al's study (10). Increasing parity has consistently been shown to reduce ovarian cancer risk in epidemiologic studies (1)(2)(3)(4)(5)(6)(7)(8), an association that was also confirmed in the current study (data not shown). More importantly, we were able to show that the risk of ovarian cancer is reduced soon after a birth and the protective effect diminished with time, consistent with the hypothesis of a pregnancy-induced clearance effect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings on pattern of relative risk for ages 25 and 35 years at delivery are consistent with the results in Pike et al's study (10). Increasing parity has consistently been shown to reduce ovarian cancer risk in epidemiologic studies (1)(2)(3)(4)(5)(6)(7)(8), an association that was also confirmed in the current study (data not shown). More importantly, we were able to show that the risk of ovarian cancer is reduced soon after a birth and the protective effect diminished with time, consistent with the hypothesis of a pregnancy-induced clearance effect.…”
Section: Discussionsupporting
confidence: 92%
“…Increasing parity has consistently been shown to reduce risk of ovarian cancer (1)(2)(3)(4)(5)(6)(7)(8). There is also epidemiologic evidence that the risk of ovarian cancer is lower in women who have an older age at first birth (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…21 Cases were 1,031 women under 79 years of age with incident ovarian cancer admitted to major teaching and general hospitals in the areas under study. Controls were 2,411 women resident in the same geographic areas and admitted to the same network of hospitals as cases for acute, non-neoplastic conditions unrelated to known or potential risk factors for ovarian cancer (26% traumas, 28% nontraumatic orthopedic disorders, 15% surgical conditions and 31% miscellaneous other illnesses).…”
Section: Methodsmentioning
confidence: 99%
“…Principal investigators from each eligible study were invited to participate. Of the 48 eligible studies identifi ed (including one multicentre international study 25,31,36 ) all but three [48][49][50] contributed to the collaboration. Individual data could not be retrieved by the investigators from two of these three studies 48,49 and investigators for the third 50 could not be located.…”
Section: Identifi Cation Of Studies and Collection Of Datamentioning
confidence: 99%